CEKAMAN OKSIDASI SEL KHAMIR Candida tropicalis YANG DIPERLAKUKAN DENGAN PARASETAMOL DAN ANTIOKSIDAN (+)-KATEKHIN [Oxidative Stress in Candida tropicalis Treated with Paracetamol and Antioxidant (+)-catechin] - Julistiono, Heddy (BERITA BIOLOGI, 2012)
In order to more understand similarity of yeast Candida tropicalis with mammalian cells in analgesic drug paracetamol metabolism and toxicity, ability of yeast in the drug metabolism and oxidative response of cells treated with the drug and (+)-catechin was studied. In mammalian cells, paracetamol toxicity is mainly caused by metabolite byproduct of drug metabolism catalyzed by cytochrome P450, a membrane-bound enzyme and peroxidase and a soluble enzyme. Previously it has been shown that paracetamol induced oxidative stress in the yeast cells; and green tea extract protected the cells from oxidation. In this study, it had been shown that paracetamol could be metabolized by yeast cell suspension or cell free extracellular protein, reflecting possibility of role of enzyme that can not be separated from cell and that is soluble, which is common phenomenon in mammalian cell system. Paracetamol of 3 mg/ml increased lipid peroxidation, a marker of oxidative stress. A green tea polyphenol, (+)-catechin of 0.1 mg/ml did not decrease lipid peroxidation content induced by paracetamol. At higher concentration (2 mg/ml), solely (+)-catechin did not increase lipid peroxidation content. Paracetamol or (+)-catechin induced slightly activity of superoxide dismutase enzyme. The data indicated that paracetamol metabolism or toxicity in the yeast may be similar to that of mammalian cells. In this condition, it suggested that (+)-catechin is one of polyphenol green tea that has weak activity of antioxidant and consequently has weak activity of prooxidant. Mechanism of paracetamol toxicity in C. tropicalis is still to be studied with emphasis on the free radical formation and drug metabolism.